INCREASING STUDENTS’ LISTENING CAPABILITY BY USING AUDIO VISUAL AT 8TH GRADE STUDENTS OF MTs AL – HIDAYAH BEKASI - DINA LUSIANA (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
This research is aimed to find out (1) the implementation of listening skills in asking and giving opinion using audio visual media at the eighth grade students‟ of MTs AL – Hidayah Bekasi in the Academic Year of 2023/2024. (2) To find out whether the use of audio visual can improve the students‟ listening skill at the eighth grade students‟ of MTs AL – Hidayah Bekasi in the Academic Year of 2023/2024. The research design of this study was Classroom Action Research (CAR). It was conducted in two cycles. Each cycle consisted of planning, action, test, observation, and documentation. The results of this research showed that (1) the implementation of audio visual media to improve students’ listening skills in asking and giving opinion as a material was going smoothly. In the process students paid attention, completed the task, more enthusiastic and not got bored quickly. The teacher also taught and gave material well. (2) There was improvement of students‟ listening skills using audio visual media. It was shown in the result of the research. The mean of pre-test and post-test cycle I was 65,5 to 69. The mean of pre-test and post-test cycle II were 72 to 85.3. The percentages the students who pass the passing grade were 25% in the pre-test I, 85.7% in the post-test I. 85.7% pre-test II, and 100% in the post-test cycle II. It showed that the students‟ percentages who got score higher than the passing grade of post-test cycle II is higher than post-test cycle I. The result of the t-test of cycle I was 3,769 and cycle II was 4,408. The t- test of cycle I and II were higher than t-table , t-test > t-table, so the result was significant. It means that the use of audio visual media improved students‟ listening skills.